PERSEPSI MAHASISWA TERHADAP KESYARIAHAN PRODUK PEGADAIAN SYARIAH - Sri Wibawani Wahyuning Astuti (Universitas Muhammadiyah Malang, 2021)
The purpose of this study is to explain students' perceptions of LKS products (in this study, PT Pegadaian Syariah) and students' interest in using LKS services after having an adequate understanding of Fiqh Muamalah in Islam. This study was followed by accounting students who took muamalah fiqh courses. In this study, qualitative descriptive analysis techniques were used with primary data through a list of open questions, so that respondents were free to answer research questions. . The results of this study are students' perceptions of Sharia Pawnshop products are definitely in accordance with sharia provisions, namely the provisions of the OJK and DSN MUI fatwas, although they did not conduct a thorough study of the application of each Sharia Pawnshop product and its contracts and pillars. customers from LKS and have never received socialization related to LKS and the products offered and After understanding the importance of sharia muamalah, it turns out that the majority are not interested in using LKS services at this time, because they feel they do not need.